Capturing Atmospheric Moisture: Towards a Local Water Catchment at the Aral Sea - Ho, Miriam (University of Waterloo, 2015)
The desertification of the Aral Sea in Central Asia is an iconic example of the devastating local consequences of large-scale water diversion. Critical of the humanitarian consequences associated with trans-boundary water diversion, this thesis seeks local solutions that work directly with the water cycle. Through first-hand photographic documentation of the city of Aral’sk, Kazakhstan, on the North Aral Sea, the thesis identifies the urban fabric as a missed opportunity for local water harvesting. The building envelope of the home serves as the site for material investigation. The thesis presents a strategy for designing a textile that passively collects moisture. It applies a promising new technology to the cultural context of Aral’sk. The textile is a projection for how building materials in the vernacular architecture of Kazakhstan might evolve to play a role in local water harvesting. Manipulating material properties to capture omnipresent but elusive water molecules from the atmosphere can temper the harsh and fragile environment of aridity, improving living conditions in the desert. The design investigations connect the performative and social functions of the building envelope. New, emerging paradigms for decentralized water management emphasize the role of water-sensitive materials and design elements in improving the local urban watershed. Materials can strategically capture, retain, and redirect water flow, encouraging water to flow through the city rather than out of it. The thesis includes a theoretical discussion of the conception of building materials as zones of dynamic energy exchange to help shift the discourse towards a more nuanced relationship with water in our immediate environment.
Keywords: Architecture